The mental health of Asian American adolescents and young adults amid the rise of anti-Asian racism - Huynh, James; Chien, Jessie; Nguyen, Amy T.; Honda, Delanie; Cho, Emily EunYoung; Xiong, Maliya; Doan, Tran T.; Ngo, Thoai D. (Frontiers in Public Health, 2023)
Objectives We describe the perceptions and experiences of anti-Asian racism and violence and depression severity prior to and during the COVID-19 pandemic among a sample of Asian American (AA) adolescents and young adults. Methods We used data from the Young Asian American Health Survey (YAAHS), an online-recruited sample of AA adolescents (ages 13–17) and young adults (ages 18–29 years) conducted during May 2021 to March 2022. We presented descriptive statistics examining the univariate distribution and bivariate relationships of depression severity, sociodemographic characteristics, and experiences and perceptions of anti-Asian violence. Results Our sample (n = 176) comprised AA adolescents and young adults from 17 Asian ethnicities. A quarter said that the frequency and/or severity of their personal experiences of anti-Asian harassment had increased since the pandemic started. 76% indicated feeling less safe now than before the pandemic. Two-thirds reported that their depressive symptoms have increased since the pandemic started. Participants who reported feeling less safe now than before the pandemic were more likely to report increased personal experiences with anti-Asian harassment and increased depression severity since the pandemic started than those who reported feeling as safe or safer before the pandemic (p < 0.01 for both). Discussion Findings illustrate AA adolescent and young adults are experiencing multiple health and social crises stemming from increased anti-Asian racism during the COVID-19 pandemic. We urge policymakers to strengthen data systems that connect racial discrimination and mental health and to institute prevention measures and anti-racist mental health services that are age- and culturally-appropriate for AA adolescent and young adults.